Extension of elliptic curve Qu–Vanstone certificates and their applications. (June 2022) - Liu, Zi-Yuan; Tseng, Yi-Fan; Tso, Raylin; Wang, Peter Shaojui; Su, Qin-Wen
Abstract: In public key infrastructure, a certificate, issued by a certificate authority (CA), is used to guarantee the connection between a user and her/his public key. In order to improve the efficiency, the concept of implicit certificate protocol is introduced by Girault and Gönther. In the existing implicit certificate protocol, a user must issue a certificate request to the CA for each key pair. However, in certain applications ( e.g., IoT, sensor networks, and cryptocurrency), a user (or a device) will have multiple public/private key pairs that are related to the same identity. Therefore, the communication cost will be linearly related to the number of key pairs the user has. Furthermore, the storage cost of a large number of certificates is not an ideal property in practice. In this paper, to address the above issues, we proposed two schemes from the most widely used elliptic curve Qu–Vanstone implicit certificate scheme (ECQV). In our first scheme, called M-ECQV I, an ECQV certificate holder, who obtains an ECQV certificate issued by the certificate authority, can further issue multiple credentials with the same identity as ECQV certificate holder and the corresponding key pairs from the ECQV certificate. In our second scheme, called M-ECQV II, it not only supports the comparable functionality of M-ECQV I, but the verifier can ensure that the credentials are only used by the ECQV certificate holder ( i.e., these credential are "self-use") to be suitable to different scenarios. In addition, the security models are well-defined and the rigorous security proofs are also given. Experimental results show that our schemes not only greatly improve the performance, but also reduce the storage cost.